First report of subfamily Scydmaeninae (Coleoptera, Staphylinidae) from Shanghai, with description of two new species - Zi-Wei Yin; Ting Feng; De-Yao Zhou (ZooKeys, 2025)
The subfamily Scydmaeninae (Coleoptera: Staphylinidae) is reported from Shanghai, China for the first time. Three species of the genus Euconnus Thomson were recognized: E. (s. str.) dulcis Sharp, 1886, E. (s. str.) imparitus sp. nov. (type locality: Waigang Town, Jiading District), and E.(s. str.) magnoculus sp. nov. (type locality: Shanghai Zoo, Hongqiao District). The new species are described, and diagnoses and illustrations of the habitus and important diagnostic features for all taxa are provided for ready identification. Furthermore, Euconnus cerastiventris Vit, 2006, syn. nov. is placed as a junior synonym of E. dulcis. A key to Euconnus species that occur in Shanghai is provided.